Repeat Acute Coronary Syndrome Following Percutaneous Coronary Intervention: A Case Report - Alief Rezkinanda; Sjaiful Anwar (Jurnal Sehat Indonesia (JUSINDO), 2026)
Percutaneous coronary intervention (PCI) is the primary reperfusion strategy for ST-elevation myocardial infarction (STEMI). Despite high procedural success rates, patients remain at risk for recurrent acute coronary syndrome (ACS), particularly those with significant comorbidities. We report a case of recurrent ACS in a patient less than one year following successful primary PCI. A 50-year-old female presented to the emergency department with typical angina, shortness of breath, nausea, and diaphoresis. Her medical history was significant for hypertension, type 2 diabetes mellitus, and a STEMI treated with primary PCI five months prior. Despite reported adherence to dual antiplatelet therapy (DAPT), she presented with tachycardia (104 bpm) and hypotension (155/55 mmHg). Electrocardiography revealed sinus tachycardia with pathological Q waves in leads V1–V4, consistent with a prior anterior myocardial infarction. Laboratory evaluation demonstrated hyperglycemia (228 mg/dL) and elevated cardiac troponin (44.2 ng/mL). The patient was diagnosed with recurrent ACS superimposed on an old anterior myocardial infarction. She was stabilized with loading doses of aspirin and clopidogrel and admitted to the Intensive Cardiac Care Unit (ICCU) for guideline-directed medical therapy, including beta-blockers and high-intensity statins. She was discharged in stable condition after five days. This case illustrates that recurrent ACS can occur shortly after successful revascularization, specifically in patients with persistent cardiovascular risk factors such as uncontrolled hyperglycemia and hypertension. It highlights the critical importance of aggressive secondary prevention, strict glycemic control, and close follow-up to mitigate the risk of adverse cardiac events in the post-PCI period.